SLIRP differentially modulates RNA binding of pathogenic LRPPRC variants - Louise Lambert; Urška Rovšnik; Amandine Moretton; Katarina Johansson; Mãdãlina Sãcultanu; Mathilde Chéron; Adèle Porcan; Bertil Macao; Siet van den Wildenberg; Xuefeng Zhu; Maria Falkenberg; Géraldine Farge (NAR Molecular Medicine, 2026)
Abstract The LRPPRC/SLIRP complex is a key post-transcriptional regulator of mitochondrial gene expression, stabilizing mitochondrial mRNAs and promoting their polyadenylation and translation. Mutations in LRPPRC cause mitochondrial disorders, including Leigh syndrome French-Canadian type (LSFC), primarily affecting oxidative phosphorylation. Here we examined the RNA-binding properties of wild-type LRPPRC and three pathogenic variants (A354V, K909del, and R1276_K1300del) using electrophoretic mobility shift assays, acoustic force spectroscopy, and AlphaFold 3 modeling. All three mutations reduced intrinsic RNA binding, with R1276_K1300del showing no detectable interaction in the absence of SLIRP. Remarkably, SLIRP restored RNA binding of this mutant to near wild-type levels, likely through conformational stabilization, as supported by single-molecule and structural analyses. These findings highlight SLIRP’s critical role in modulating LRPPRC function and suggest that enhancing SLIRP activity represents a potential therapeutic strategy for LRPPRC-related mitochondrial disorders.